The Oxford handbook of illiberalism - Laruelle, Marlène 1972- HerausgeberIn (Oxford handbooks online, 2023)
This handbook is currently in development, with individual articles publishing online in advance of print publication. At this time, we cannot add information about unpublished articles in this handbook, however the table of contents will continue to grow as additional articles pass through the review process and are added to the site. Please note that the online publication date for this handbook is the date that the first article in the title was published online.